2011
DOI: 10.1149/1.3569106
|View full text |Cite
|
Sign up to set email alerts
|

Monochlorosilane for Low Temperature Silicon Epitaxy

Abstract: Silane (SiH 4 ) and dichlorosilane (DCS) are currently the precursors of choice for Silicon Vapor Phase Epitaxy at low temperatures (T < 1000 C). But device innovation is pushing down process thermal budgets to the extent that it becomes apparent that in the near future poor Si growth rates will become a roadblock for high volume manufacturing. Therefore, new precursors that produce high growth rates at low deposition temperatures (<650 C) are needed for advanced epitaxial applications, such as recessed sour-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In this regime, the growth rate is limited by the desorption of former hydrogen ligands. The trendline is fitted with eq , where GRS is the simulated film growth rate, k is a temperature independent frequency factor in nm/min, E is the activation energy, R is the ideal gas constant, T is the temperature, N is an atomic density, C is the precursor concentration in the gas phase, p SiH 4 0 is the precursor partial pressure, and finally, α is an empirical reaction order . The acronym GRS, standing for Growth Rate Simulated, is used to discriminate theory from experiments.…”
Section: Experiments and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regime, the growth rate is limited by the desorption of former hydrogen ligands. The trendline is fitted with eq , where GRS is the simulated film growth rate, k is a temperature independent frequency factor in nm/min, E is the activation energy, R is the ideal gas constant, T is the temperature, N is an atomic density, C is the precursor concentration in the gas phase, p SiH 4 0 is the precursor partial pressure, and finally, α is an empirical reaction order . The acronym GRS, standing for Growth Rate Simulated, is used to discriminate theory from experiments.…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…The acronym GRS, standing for Growth Rate Simulated, is used to discriminate theory from experiments. There is a large body of experimental results showing α = 1 for silane. , An activation energy of about 193 kJ/mol is commonly reported, but large variations across studies are also noted …”
Section: Experiments and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] In addition, there are some reports about CVD using trichlorosilane (SiHCl 3 ) and monochlorosilane (SiH 3 Cl). 5,6) Although the influence of the Cl-introduction to molecular structures has been discussed, there has been a lack of discussion on the difference of the characteristics of the gas-phase reaction between SiH x Cl 4−x (x = 0 ∼ 3) gases. First-principles calculations and kinetics studies for these chlorosilanes have been reported.…”
mentioning
confidence: 99%
“…However, it was reported that SiH 2 Cl 2 has a lower silicon growth rate than SiH 3 Cl in the range of 600 °C-850 °C. 6) SiH 3 Cl has a much lower equilibrium partial pressure of HCl, thus, it is expected that silicon growth using SiH 3 Cl gas has a lower effect of etching by HCl and the silicon growth rate is higher than SiH 2 Cl 2 . In cases where the HCl effects need to be reduced in a deposition process, SiH 3 Cl can be a better source gas.…”
mentioning
confidence: 99%